Aplikasi Penjadwalan Sidang Tugas Akhir di Fakultas Teknologi Informasi Universitas Kristen Maranatha Dengan Metode Depth First Search - Yulius Bastian; Daniel Jahja Surjawan; Adelia Adelia (Maranatha University Press, 2018)
Every student in all Universities who is already in the final semester will report the results in the form of presentation in the presence of mentors and examiners. Students will usually wait for a schedule that has been determined by the coordinator in the Faculty. This scheduling sometimes makes students anxious because they have to wait until the time is appropriate and often they don’t get a suitable schedule. This also happens with the students in Faculty of Information Technology, Maranatha Christian University. The coordinators often experience difficulties in the allocation of mentors or examiners to be scheduled for a council. This research will make an application that help in conducting scheduling of the council so that the council process can be held smoothly and students will not be afraid to miss the schedule. Applications will be built using JavaFX desktop programming, JSON type network services, and data reporting through JasperReport. Data were collected in literature and interviews with related parties. Applications will accommodate from data entry, role assignment determination, scheduling, and reporting. Applications use data exchange methods through network services that facilitate the development of data needs. This prototype has been tested by black box method. The test results state that this prototype works through testing with all of the possibilities.